13x+1+12x+9=

Simple and best practice solution for 13x+1+12x+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x+1+12x+9= equation:


Simplifying
13x + 1 + 12x + 9 = 0

Reorder the terms:
1 + 9 + 13x + 12x = 0

Combine like terms: 1 + 9 = 10
10 + 13x + 12x = 0

Combine like terms: 13x + 12x = 25x
10 + 25x = 0

Solving
10 + 25x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 25x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 25x = 0 + -10
25x = 0 + -10

Combine like terms: 0 + -10 = -10
25x = -10

Divide each side by '25'.
x = -0.4

Simplifying
x = -0.4

See similar equations:

| t/t=-9/1 | | 10x-4-6x=-84 | | 9x-81=7 | | .3+.6=.06 | | 4/24 | | (-6)(-6)= | | 24/.4 | | 19=3t-23 | | 3(3m+4)-2(m-7)=0 | | 6d-18+2=2 | | 24/.04 | | 12x+12x+16+10x-4=102 | | -20=-4q | | b^3+15b^2-904=0 | | -10t=90 | | 0.4/24 | | [7-2y]-8=-3 | | 2x^2-22x-12=0 | | -2[d+6]=-10 | | (-15)(-17)= | | x/5=x/3-2 | | -8x+2+5x=-13 | | 6x-(3x-8)=29 | | -6+-8g=-62 | | b^3+b^2+1=0 | | 5=d+6 | | -80=8(b-5)-10(b+6) | | 10k^2-24=-12k | | -18-4a=-2 | | 20x+5x+1=101 | | x-9/10=21/10 | | (2y-5)/(6x-7y)=x |

Equations solver categories